Assessment of Housing for Low-income Groups in Danang : Phase I Report - World Bank (Washington, DC, 2013)
Danang City is the capital and economic hub of the central region of Vietnam. As in all of the major urban centers of the country, Danang is currently experiencing rapid urbanization fueled by consistent economic growth and the resultant steady increase in population, much through rural-urban migration. For this reason, central and city government has been increasingly concerned with the urban development and housing sectors. The objective of the (LIHAS) Study is to undertake an assessment of the low-income housing sector in Danang with a view to: i) determining effective demand for low-income shelter in Danang; and ii) providing alternative models of housing production, including aspects of housing finance, construction and maintenance. The Study will take account of Government housing policy as it affects low-income households (LIH) in Danang. In this regard there has been a move away from direct Government involvement in house construction for the public sector service which was found to be financiallyunsustainable. The scope of work is based on two phases as follows: Phase I. Data Collection and Analysis: this will involve: i) agreement with the DPC on adefinition low-income households for Danang City to be used as basis for the Study; ii) a literature review of relevant reports and studies; iii) preparation of an inventory of all existing publicly constructed housing developments for low-income groups in Danang built since 1980; iv) a rough assessment of the current size and rate of expansion of informal housing in the City; v) an assessment of the type and level of private sector participation in low income housing provision; vi) a review and assessment of the roles and responsibilities of both DONRE and DOC in respect to the provision and maintenance of publicly sponsored low-income housing; vii) a financial assessment of DONRE and DOC operations withrespect to the provision and maintenance of low-income housing; viii) identification of the binding constraints on the creation of low-income housing generally and in Danang specifically.